Is "periodization programming" periodization or programming? - Hammert, W. B.; Kataoka, R.; Vasenina, E.; Ibrahim, A. H.; Bruckner, S. L. (Journal of Trainology, 2021)
Within the literature examining the periodization of resistance training, "periodization" and "programming" are often confused and used interchangeably. This has resulted in the drawing of inferences regarding the efficacy of periodization from training studies comparing different programming models over short periods of time. As this conflation has become an area of scientific discussion, what was once referred to as "periodization" is now often referred to as "periodization programming" or "periodized programming." Presumably, the use of the term "periodization programming" acknowledges the shortterm nature of a given research intervention. However, this term has never been explicitly defined in the scientific literature. Furthermore, it is unclear if "periodization programming" is actually a form of periodization. Objectives: To define "periodization programming" and to discuss its use within the literature. Design & Methods: Literature including the terms "periodization programming" and "periodized programming" were reviewed. Results: Deliberate manipulations in the volume and training load over the short-term seem to be defining characteristics of "periodization programming." The resistance training methods employed by "periodization programming" studies share common ground such that they are structured in a manner resembling one stage of a block periodization model and are carried out alongside other stressors. Conclusions: "Periodization programming" studies are similar to previous studies employed to examine the concept of periodization and thus, may more accurately be investigating resistance training at the programming level. Without a formal definition, these studies may add to the confusion within the literature and further challenge the ability to draw inferences surrounding the efficacy of periodization.